Accelerating The Halal Industry Sector To Realize Indonesia As The World Halal Center - Kadir, Syahruddin; Alaaraj, Hassan (El-Qish: Journal of Islamic Economics, 2023)
The purpose of this study is to identify the condition of the halal industry and the opportunity aspects of the halal industry sectors in Indonesia. This research uses a qualitative descriptive method with an exploratory approach through secondary data collection. Findings. First, the condition of the halal industry according to the release of the State of the Global Islamic Economic Report 2022 shows that Indonesia's position globally ranks 4th (four) and this will continue to increase along with Indonesia having the largest Muslim population in the world, making it an important market for halal products and services. Second; 7 important sectors must be utilized including food and beverage, fashion, tourism and hospitality, pharmaceuticals, Islamic finance, media and recreation, and halal supply chain. These sectors are maximally utilized in building consumer confidence, forming halal lifestyle awareness, and increasing sharia understanding to expand the range of halal industry services so that Indonesia can become the world's halal center.